2018
DOI: 10.1038/s41598-018-28952-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific pattern of berberine pleiotropic effects on different human cell lines

Abstract: The natural alkaloid berberine has several pharmacological properties and recently received attention as a potential anticancer agent. In this work, we investigated the molecular mechanisms underlying the anti-tumor effect of berberine on glioblastoma U343 and pancreatic carcinoma MIA PaCa-2 cells. Human dermal fibroblasts (HDF) were used as non-cancer cells. We show that berberine differentially affects cell viability, displaying a higher cytotoxicity on the two cancer cell lines than on HDF. Berberine also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…In addition, the decrease in the proportion of S phase cells suggested that cell proliferation was inhibited by the treatments. The data also showed that the berberineñmatrine combination had a more significant effect than either drug alone (34)(35).…”
Section: Compound-induced Cell Cycle Arrest In Cervical Cancer Cellsmentioning
confidence: 84%
“…In addition, the decrease in the proportion of S phase cells suggested that cell proliferation was inhibited by the treatments. The data also showed that the berberineñmatrine combination had a more significant effect than either drug alone (34)(35).…”
Section: Compound-induced Cell Cycle Arrest In Cervical Cancer Cellsmentioning
confidence: 84%
“…G2/M arrest in U343 cells and G1 arrest in MIA PaCa-2 cells were induced by the treatment with 50 μM BBR for 48 hr. 86 Furthermore, with 24-hr treatment of U266 cells with 40, 80, 120, and 160 μmol/L of BBR, the number of cells in the S phase was decreased and the number of cells in the G2/M phase went clearly higher when compared to the untreated controls. These findings suggested that BBR could inhibit the proliferation of multiple myeloma cells and caused cell cycle arrest.…”
Section: Bbr and Cell Cycle Arrestmentioning
confidence: 91%
“…These findings, thus, indicated that BBR-induced KB cell death is controlled by both extrinsic and intrinsic mitochondrialmediated apoptotic signaling pathways. 85 Agnarelli et al 86 studied MIA PaCa-2 panceratic adenocarcinoma and U343 glioblastoma cells for 48 hr with 50 μM BBR and found that in U343 cells, the activity of caspase-3 decreased and in MIA PaCa-2 cells increased. Moreover, the utilization of BBR in treating HCT-15 colorectal adenocarcinoma cells enhanced the spliced caspase-3 and Bax expression and substantially reduced the expression of surviving and BCL-2 which ultimately caused apoptosis.…”
Section: Bbr Induces Apoptosismentioning
confidence: 99%
“…The mode of cell growth inhibition and induction of cell death in cancer cells by berberine has been extensively shown to involve apoptosis. This is largely based on induction of mitochondrial dysfunction as shown by changes in mitochondrial permeability and/or membrane potential (∆ψm) and caspase-dependent cell death [28,35,39,57,61]. As a marker of apoptosis, genes and proteins which are known to induce apoptosis in cancer cells (Bax, Bak, Bad, Apaf-1; Fas, FasL and tumour necrosis factor-α (TNF-α)) are upregulated while those associated with cell survival (Bcl-2 and Bcl-xL, survivin) are suppressed [24,35,40,42,47,49,[55][56][57][58][59]61,63].…”
Section: The Anticancer Effect Of Berberine: Direct Cytotoxicity In Cmentioning
confidence: 99%